Establishment of a human induced pluripotent stem cell line (NIHTVBi031-A) derived from a COPA syndrome patient with a heterozygous p.Ala239Pro mutation - Joseph, Benjamin; Varea, Isabella; Emmerich, Kevin; Manohar-Sindhu, Sahana; Zou, Jizhong; Friend, Kip; Sipwoli, Caleb; Tang, Xuming; Yang, Dan; de Jesus Rasheed, Adriana A; Goldbach-Mansky, Raphaela; Boehm, Manfred (Stem cell research, 2024)
We have successfully generated human induced pluripotent stem cells (hiPSC) from peripheral blood mononuclear cells (PBMCs) of a patient with COPA Syndrome. The patient, a 6 year old Caucasian male, has a spontaneous de novo missense mutation that replaced alanine with proline in the COPA gene. This paper confirms the differentiation potential of the hiPSC line, the presence of the p.Ala239Pro mutation, and the expression of typical pluripotency markers within the hiPSC line. The hiPSC line is ready for use as a cellular model of COPA Syndrome.